Mass spectrometry imaging for visualizing organic analytes in food. Issue 6 (28th March 2014) - Handberg, Eric; Chingin, Konstantin; Wang, Nannan; Dai, Ximo; Chen, Huanwen
<x xml:space="preserve">Abstract</x> The demand for rapid chemical imaging of food products steadily increases. Mass spectrometry (MS) is featured by excellent molecular specificity of analysis and is, therefore, a very attractive method for chemical profiling. MS for food imaging has increased significantly over the past decade, aided by the emergence of various ambient ionization techniques that allow direct and rapid analysis in ambient environment. In this article, the current status of food imaging with MSI is reviewed. The described approaches include matrix‐assisted laser desorption/ionization (MALDI), but emphasize desorption atmospheric pressure photoionization (DAPPI), electrospray‐assisted laser desorption/ionization (ELDI), probe electrospray ionization (PESI), surface desorption atmospheric pressure chemical ionization (SDAPCI), and laser ablation flowing atmospheric pressure afterglow (LA‐FAPA). The methods are compared with regard to spatial resolution; analysis speed and time; limit of detection; and technical aspects. The performance of each method is illustrated with the description of a related application. Specific requirements in food imaging are discussed. © 2014 Wiley Periodicals, Inc. Mass Spec Rev 34: 641–658, 2015.